Industrial policy reforms an assessment. - Sharma, O.P.
"The basic purpose of this paper is to analyse the trends and implications of developments in industrial policy since the beginning of the 1980s. The analysis begins in Section 1 with a brief description of the major policy changes announced in 1985. Some evidence is provided on the record of growth in the ensuing period of the Seventh Plan (1985-90) with a view to critically examine whether the reforms made any perceptible impact on the industrial sector. Thereafter, in Section II an attempt is made to update the status of policy reforms and to analyse the implications on industrial production since mid-1991. The paper ends in Section III with concluding remarks and suggestions on some pertinent issues concerning the emerging industrial scene"
Keywords: Industry and state - India